Effects of the preparation, curing and hygrothermal conditions on the viscoelastic response of a structural epoxy adhesive. (October 2021) - Cruz, Ricardo; Correia, Luís; Cabral-Fonseca, Susana; Sena-Cruz, José
Abstract: This paper addresses the viscoelastic behaviour of a commercially available cold-curing structural epoxy adhesive, under different preparation, curing and hygrothermal conditions. The main parameters studied were the preparation method (influence of the degassing and the temperature of the initial curing), the creep stress level, and the hygrothermal conditions. Tensile creep tests last up to 2400 h. Test results revealed that the preparation method has great influence on the tensile properties of the adhesive, particularly on the viscoelastic response where degassing and curing at 20 °C showed lower creep deformations. Specimens under 98% of relative humidity faced tertiary creep and then rupture. For the adopted levels of creep stress, the adhesive shows a linear creep behaviour, being parameterized using the Burgers and the modified Burgers equations.